Charlie Chan's Murder cruise - White, Robertson, 1900-1985.; Ziffren, Lester; Forde, Eugene, 1898-1986.; Wurtzel, Sol M., 1890-1958.; Larkin, John, 1912-1965.; Foster, Norman, 1900-1976.; Toler, Sidney, 1874-1947.; Weaver, Marjorie, 1913-1994.; Atwill, Lionel, 1885-1946.; Yung, Victor Sen.; Lowery, Robert, 1916-1971.; Beddoe, Don.; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2008)
Charlie Chan's Murder cruise: When a trusted colleague requests assistance in investigating a murder on a high- society pleasure cruise, the unflappable sleuth Charlie Chan is all too happy to help.
Charlie Chan in Panama: Crime solver Charlie Chan is busily working undercover in the volatile wartime region of Panama, which is rife with spies and conspirators. He uncovers a sinister plot to blow up the Panama Canal and destroy the U.S. naval fleet.
Charlie Chan's Murder cruise (1940 ; 76 min.) -- Charlie Chan in Panama (1940 ; 68 min.)
Title from container.
Based on the characters created by Earl Derr Biggers.
Charlie Chan's Murder cruise originally released as a motion picture in 1940 ; Charlie Chan in Panama originally released as a motion picture in 1940.
Director of photography, Virgil Miller.
Charlie Chan's Murder cruise cast: Sidney Toler, Marjorie Weaver, Lionel Atwill, Sen Yung, Robert Lowery, Don Beddoe.
Charlie Chan in Panama cast: Sidney Toler, Jean Rogers, Lionel Atwill, Mary Nash, Sen Yung, Kane Richmond, Chris- Pin Martin.
Keywords: Chan, Charlie (Fictitious character) -- Drama; Murder -- Investigation -- Drama; Ocean travel -- Drama; Criminal investigation -- Drama; Charlie Chan films; Thrillers (Motion pictures); Crime films; Feature films; Video recordings for the hearing impaired; Panama Canal (Panama) -- Drama